2020
DOI: 10.3389/fbioe.2019.00476
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Isomerase and Weimberg Pathway for γ-PGA Production From Xylose by Engineered Bacillus subtilis

Abstract: The production of poly-γ-glutamic acid (γ-PGA), a biopolymer consisting of D-and L-glutamic acid monomers, currently relies on L-glutamate, or citrate as carbon substrates. Here we aimed at using plant biomass-derived substrates such as xylose. γ-PGA producing microorganisms including Bacillus subtilis natively metabolize xylose via the isomerase pathway. The Weimberg pathway, a xylose utilization pathway first described for Caulobacter crescentus, offers a carbon-efficient alternative converting xylose to 2-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Modified Bradford Protein Assay Kit (Sangon Biotech, Shanghai, China) was used to measure the protein content. The γ-PGA content was detected based on CTAB assay with incubation time adjusted to 10 min [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Modified Bradford Protein Assay Kit (Sangon Biotech, Shanghai, China) was used to measure the protein content. The γ-PGA content was detected based on CTAB assay with incubation time adjusted to 10 min [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…This observation is claimed to be the first demonstration of a functional Weimberg pathway in fungi. Halmsschlag et al [87] compared the production from xylose of poly-γ-glutamic acid by the isomerase and Weimberg pathways by a genetically engineered strain of B. subtilis, and showed that the limiting diauxic growth in the strain could be overcome by the addition of glucose, resulting in high-yield production of the polymer from biomass substrates. Borgström et al [86] described the channelling of xylose by S. cerevisiae through the pentose phosphate pathway and into glycolysis.…”
Section: D-xylose Metabolismmentioning
confidence: 99%
“…One uses the power input measurement during the cultivation, which allows the calculation of the viscosity 33 . The other one is the recently published Viscosity Monitoring Online System (ViMOS), which optically measures the cultivation broth viscosity 34 and has already been used to analyze γ‐PGA production 35 . The power input measurement method is based on the effect of viscosity changes on the power input in unbaffled shake flasks 36,37 .…”
Section: Introductionmentioning
confidence: 99%
“…33 The other one is the recently published Viscosity Monitoring Online System (ViMOS), which optically measures the cultivation broth viscosity 34 and has already been used to analyze γ-PGA production. 35 The power input measurement method is based on the effect of viscosity changes on the power input in unbaffled shake flasks. 36,37 An increase of fermentation broth viscosity results in an increase of the power input.…”
Section: Introductionmentioning
confidence: 99%